The relationship between shift work and quality of sleep among nurses in UMMC - Rabiatul Adawiyah, Roslan (2019)
This study was carried out with the purpose to investigate the relationship between shift work status and quality of sleep among nurses in Surgery Department at University Malaya Medical Centre. Nurses perform an important role in patient cf re. They are the first person to detect and noticed any changes in patient condition and patient health status. Nurses also act as a supporter in terms of physical and emotional well -being of the patient during ongoing treatment. Therefore, this study held among nurses to access nurses ' quality of sleep. Therefore, to investigate the sleep quality and its relations to shift work a Pittsburgh Sleep Quality Index questionnaire was used. The aim of this study I was to investigate the level of sleep quality, differences between demographic factors and the relationship between shift works and sleep quality. Data was collected using a self-reported questionnaire and was analysed using SPSS Statistics Version 23 .0. Sample for this study included a total of 97 participants. Findings show that participants whichever doing shift work or not are no significant differences with sleep quality and working in shift work also is not associated with poor sleep quality. From the result also, it can be seen that 17.6% of nurses working in the Surgery Department in UMMC are having poor sleep quality'. It is can be concluded that regardless of working in shift work or standard shift nursed still have poor sleep quality. Further research with different variables needs to be carried + t to study factors that affected sleep quality among nurses. A higher number of respondents and hospitals will be more significant for future research and could generate more distinct results. To increase the sample size, the inclusion of areas with more multiple diciplines and multiple staff is suggested.